2008
DOI: 10.1002/jmr.896
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of T‐cell receptor–peptide/MHC interactions: progress and opportunities

Abstract: αβ T cell receptors (TCR) recognize peptide antigens presented by class I or class II major histocompatibility complex molecules (pMHC). Here we review the use of thermodynamic measurements in the study of TCR-pMHC interactions, with attention to the diversity in binding thermodynamics and how this is related to the variation in TCR-pMHC interfaces. We show that there is no enthalpic or entropic signature for TCR binding; rather, enthalpy and entropy changes vary in a compensatory manner that reflects a narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
77
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 114 publications
13
77
0
Order By: Relevance
“…First, the MEL5/ A2-ELA interaction is the only enthalpically unfavorable TCR interaction ever described (49). Second, the MEL5⅐A2-ELA complex has the lowest buried surface area (1,226 Å 2 ) of any published TCR⅐pMHC complex, an observation that is supported by the relatively small ⌬Cp 0 value (Ϫ0.14 kcal/mol⅐K).…”
Section: Discussionmentioning
confidence: 92%
“…First, the MEL5/ A2-ELA interaction is the only enthalpically unfavorable TCR interaction ever described (49). Second, the MEL5⅐A2-ELA complex has the lowest buried surface area (1,226 Å 2 ) of any published TCR⅐pMHC complex, an observation that is supported by the relatively small ⌬Cp 0 value (Ϫ0.14 kcal/mol⅐K).…”
Section: Discussionmentioning
confidence: 92%
“…The lysozyme epitope consisted of three sequentially separated regions. A shallow groove accommodated positively charged Arg 45 and Arg 48 of lysozyme that were complemented by two negative Glu residues in the antibody heavy chain (Glu 35 of H1 and Glu 50 of H2) (Fig. 2).…”
Section: Historical Developmentmentioning
confidence: 99%
“…Although MHC class I and class II molecules are very similar in structure, this difference probably contributes to the ability of subsets of T cells to distinguish presentation by the two MHC classes of molecules [46]. More recently, it has been shown that TCR binding to peptide-MHC class I complexes can be quite flexible, with CDR loop movements > 0.5 nm [47], and dominated by enthalpic (electrostatic) interactions despite unfavorable entropic changes [48], although certainly other binding strategies are used.…”
Section: Historical Developmentmentioning
confidence: 99%
“…The next series of pictures show initially a view of the entire AMF complex with the six complementarity determining regions (CDR) of Hyb3 (views 9, 10), then zoom into the contact area (view 11), depict the conformations of the four above-mentioned HC residues in liganded as well as unliganded form together with the a1-and a2 domains of the two structures superimposed (views 12, 13), and finally concentrate on the MAGE-A1 peptide that exhibits two slightly distinct conformations when AM and AMF are compared (views [14][15][16], before the AM complex is shown again (views 17, 18).…”
Section: Structural Features Of the Hla-a1:mage-a1 Complexmentioning
confidence: 99%
“…To some extent, the binding of the in vitro affinity-matured Hyb3 resembles that of a soluble TCR or KIR, but Hyb3 exhibits a $1000 times higher affinity toward its target than a typical TCR or KIR. [2][3][4]15 In attempting to understand the basis for this finding, we focus here on changes induced by Hyb3 in the conformation of pMHC residues by comparing the Hyb3-liganded structure (A1:MAGE-A1:Fab-Hyb3, AMF) with that of the newly determined, unliganded HLA-A1:MAGE-A1 complex (AM). The results reveal that four residues, at positions 65, 72, 145, and 146 of the HC, undergo highly significant changes in their side chain orientations because of the interaction with Hyb3.…”
Section: Introductionmentioning
confidence: 99%